This integral seems to produce a neat closed form

We seek to prove that

$$2e^2\int_{0}^{\infty} {x\ln x\over 1-e^{2e\pi{x}}}\mathrm dx=\ln A\tag1$$

Where A is Glaisher Kinkelin Constant

An attempt:

Recall $(2)$

$${x\over e^x-1}=\sum_{n=0}^{\infty}{B_nx^n\over n!}\tag2$$

Then $(1)$ becomes

$$-2e^2\sum_{n=0}^{\infty}{B_n\over n!}\cdot{(2e\pi)^n}\color{red}{\int_{0}^{\infty}x^{n+1}\ln x\mathrm dx}\tag3$$

red part diverges.

Or rewrite $(1)$ as

$$e^2\int_{0}^{\infty}\left({x\ln x\over 1-e^{e\pi{x}}}+{x\ln x\over 1+e^{e\pi{x}}}\right)\mathrm dx\tag4$$

Recall $(5)$

$$\zeta(s)={1\over \Gamma(s)}\int_{0}^{\infty}{x^{s-1}\over e^x-1}\mathrm dx\tag5$$

Go this far, no idea where to go from here.

  • 1
    $\begingroup$ By regularization of a divergent series the limit defining $A$ is related with $\zeta'(-1)$. By the reflection formula for the $\zeta$ function we have that $\zeta'(-1)$ is related with $\zeta'(2)$, and by a substitution and differentiation under the integral sign your integral just depends on $\zeta'(2)$. $\endgroup$ – Jack D'Aurizio Mar 30 '17 at 13:07

In $(1)$, let $2e\pi x=u$ to get

$$I=2e^2\int_0^\infty\frac{x\ln(x)}{1-e^{2e\pi x}}\ dx=\frac1{2\pi^2}\int_0^\infty\frac{u\ln(u)-u\ln(2e\pi)}{1-e^u}\ du$$

Then notice that

$$\int_0^\infty\frac{x^{s-1}}{e^x-1}\ dx=\zeta(s)\Gamma(s)$$

By differentiating under the integral, we also find that

$$\int_0^\infty\frac{x^{s-1}\ln(x)}{e^x-1}\ dx=\frac d{ds}\zeta(s)\Gamma(s)=\zeta'(s)\Gamma(s)+\zeta(s)\Gamma'(s)$$

And thus,


You may find derivatives of the Riemann zeta function here and the derivative of the Gamma function is merely the digamma function.


I will note $I$ the quantity you want to evaluate. I guess the first think to do is a sustitution $y=ex$. You get $$I = 2 \int_0^{+\infty}\frac{y(\ln(y)-1)}{1-e^{2\pi y}}dy=2 \left(\int_0^{+\infty}\frac{y}{e^{2\pi y}-1}dy-\int_0^{+\infty}\frac{y\ln(y)}{e^{2\pi y}-1}dy \right).$$ According to your link, we have $$\int_0^{+\infty}\frac{y\ln(y)}{e^{2\pi y}-1}dy=\frac{1}{24}-\frac{1}{2}\ln(A).$$ So, we just have to prove that $$\int_0^{+\infty}\frac{y}{e^{2\pi y}-1}dy=\frac{1}{24}$$ to get the conclusion. To compute this, set $u = 2\pi y$. You get $du = 2\pi dy$. Hence $$ \int_0^{+\infty}\frac{y}{e^{2\pi y}-1}dy =\frac{1}{4\pi^2}\int_0^{+\infty} \frac{u}{e^u-1}du=\frac{1}{4\pi^2}\Gamma(2)\zeta(2).$$ Hence the conclusion, since $\zeta(2) = \frac{\pi^2}{6}.$

  • $\begingroup$ For the last integral, why not use $u = 2\pi y$ and then use $(5)$ in OP's post? $\endgroup$ – N3buchadnezzar Mar 30 '17 at 12:44
  • $\begingroup$ Yes of course , I'll edit. $\endgroup$ – C. Dubussy Mar 30 '17 at 12:55

Sketch of the proof

\begin{align*} -2e^2\int_{0}^{\infty} {x e^{-2e\pi x}\log x\over 1-e^{-2e\pi{x}}}\mathrm dx &= -2e^2\sum_{n=0}^\infty\int^\infty_0 xe^{-2e\pi x (n+1)} \log(x)\mathrm dx \tag{1} \\&=-2e^2\sum_{n= 1}^\infty\frac{\psi(2)-\log(2e\pi n)}{(2e\pi)^2 n^2} \tag{2} \\&= \frac{\log(2e\pi)\zeta(2)-\psi(2)\zeta(2)-\zeta'(2)}{2\pi ^2}\tag{3} \\&= \frac{1}{12}-\zeta'(-1)\tag{4} \\&=\log A\tag{5} \end{align*}

Proof of (1)

Use the series expansion

$$\frac{1}{1-e^{2\pi e x}}={e^{-2e\pi x}\over 1-e^{-2e\pi{x}}} = \sum_{n=0}^\infty e^{-2\pi e x (n+1)}=\sum_{n=1}^\infty e^{-2\pi e x n}$$

Proof of (3)

Start by the definition of the gamma function $$\int^\infty_0 x^{v-1} e^{-sx}\,dx = \frac{1}{s^v}\int^\infty_0 x^{v-1} e^{-x}\,dx= \frac{\Gamma(v)}{s^v}$$

By differentiation we have

$$\int^\infty_0 x^{v-1} e^{-sx} \log(x)\,dx = \frac{\Gamma(v)\psi(v)-\log(s)}{s^v}$$

Let $v=2$

$$\int^\infty_0 x e^{-sx} \log(x)\,dx = \frac{\psi(2)-\log(s)}{s^2}$$

Proof of (4)

Use the functional equation

$$\zeta(s)=2^s\pi^{s-1}\sin \left( \frac{s\pi}2\right) \Gamma(1-s)\zeta(1-s)$$

By taking the derivative

$$\zeta'(s)=2^s\pi^{s-1}\log(2\pi)\sin \left( \frac{s\pi}2\right) \Gamma(1-s)\zeta(1-s)+\frac{\pi}{2}2^s\pi^{s-1}\cos\left( \frac{s\pi}2\right) \Gamma(1-s)\zeta(1-s)-2^s\pi^{s-1}\sin \left( \frac{s\pi}2\right) \Gamma(1-s)\psi(1-s)\zeta(1-s)-2^s\pi^{s-1}\sin \left( \frac{s\pi}2\right) \Gamma(1-s)\zeta'(1-s)$$

Take $s \to -1$

$$\zeta'(-1)=-2^{-1}\pi^{-2}\log(2\pi)\zeta(2)+2^{-1}\pi^{-2}\Gamma(2)\psi(2)\zeta(2)+2^{-1}\pi^{-2} \Gamma(2)\zeta'(2)$$

$$2\pi^2\zeta'(-1)=-\log(2\pi)\zeta(2)+\psi(2)\zeta(2)+ \zeta'(2)$$

By some rearrangements and adding $\log(e)=1$

$$\frac{\log(2e\pi)\zeta(2)-\psi(2)\zeta(2)-\zeta'(2)}{2\pi ^2} = \frac{1}{12}-\zeta'(-1)$$

Proof of (5)

Start by the definition

$$\zeta(s) = \lim_{m \to \infty} \left( \sum_{k=1}^{m} k^{-s} - \frac{m^{1-s}}{1-s} - \frac{m^{-s}}{2} + \frac{sm^{-s-1}}{12} \right) \ , \ \text{Re}(s) >-3.$$

Differentiate with respect to $s$

$$\zeta'(s) = \lim_{m \to \infty} \left(- \sum_{k=1}^{m} k^{-s}\log(k) - \frac{m^{1-s}}{(1-s)^2} +\frac{m^{1-s}}{1-s}\log(m)+\frac{m^{-s}}{2}\log(m)\\ + \frac{m^{-s-1}}{12}-\frac{m^{-s-1}}{12}\log(m)\right) $$

Now let $s \to -1$

$$\zeta'(-1) = \lim_{m \to \infty} \left(- \sum_{k=1}^{m} k\log(k) - \frac{m^{2}}{4} +\frac{m^{2}}{2}\log(m)+\frac{m}{2}\log(m)\\ + \frac{1}{12}-\frac{1}{12}\log(m)\right) $$

Take the exponential of both sides

$$e^{\zeta'(-1)}= e^{1/12}\lim_{m \to \infty} \frac{m^{m^2/2+m/2-1/12} e^{-m^2/4}}{ e^{\sum_{k=1}^{m} k\log(k)}} = e^{1/12}\lim_{m \to \infty} \frac{m^{m^2/2+m/2-1/12} e^{-m^2/4}}{ e^{\sum_{k=1}^{m} k\log(k)}} = \frac{ e^{1/12}}{A} $$

We conclude that

$$\zeta'(-1) = \frac{1}{12}-\log A$$

  • $\begingroup$ Thank you for the detailed explanation @zaid. $\endgroup$ – gymbvghjkgkjkhgfkl Apr 2 '17 at 4:28
  • $\begingroup$ @Bui, you are welcome. If yo have any doubt dont histate to ask. $\endgroup$ – Zaid Alyafeai Apr 2 '17 at 4:34
  • $\begingroup$ Could you please give a reference/link to the derivation of the first equation in Proof of (5)? $\endgroup$ – Hans Jun 15 '17 at 21:43

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.